2020
DOI: 10.1016/j.jaci.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the clinical effect of grass allergen peptide immunotherapy after the second and third grass pollen seasons

Abstract: Immunotherapy with grass allergen pep des provides long-las ng clinical benefit for up to 2 years a er treatment 25 days 14-week treatment period Follow-up assessments 42% symptom improvement P = .0346 Change in rhinoconjunc vi s symptoms over placebo were assessed in the Environmental Exposure Unit (EEU) over 4 rye grass pollen challenges 4 Post-treatment EEU challenges One 6 nmol pep de injec on every 2 weeks One 12 nmol pep de injec on every 4 weeks 24% symptom improvement P = .2597

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…48 Campbell and colleagues confirmed that this approach generates IL-10 + regulatory T cells capable of "linked" suppression of the response to distinct T cell epitopes within the same allergen. 66 Similar observations have been made in SP-AIT studies of bee venom, 67 grass allergen 39,40 and peanut allergy. 68 The induction of IL-10-secreting T cells in these SP-AIT studies is important since these Tr1 cells are known to promote IgG 4 production.…”
Section: Cops Vs Spssupporting
confidence: 73%
See 4 more Smart Citations
“…48 Campbell and colleagues confirmed that this approach generates IL-10 + regulatory T cells capable of "linked" suppression of the response to distinct T cell epitopes within the same allergen. 66 Similar observations have been made in SP-AIT studies of bee venom, 67 grass allergen 39,40 and peanut allergy. 68 The induction of IL-10-secreting T cells in these SP-AIT studies is important since these Tr1 cells are known to promote IgG 4 production.…”
Section: Cops Vs Spssupporting
confidence: 73%
“…Phase 1-3 clinical trials have been conducted to investigate the efficacy and safety of peptide AIT for allergic airway diseases. These have mainly focussed on major allergens including birch pollen, 36,37 grass pollen [38][39][40][41][42][43][44] or cat. [45][46][47][48][49][50][51][52][53][54][55][56] The main approach taken in these studies has been to administer SPs or COPs over 4-6 weeks, either starting at a relatively low dose with structured escalation to reach a target cumulative dose or by delivering a fixed pre-determined dose administered weekly or fortnightly.…”
Section: Framework For Peptide Aitmentioning
confidence: 99%
See 3 more Smart Citations